Penggunaan Alat Permainan Edukatif sebagai Media Pembelajaran dalam Kegiatan Bermain sambil Belajar - Affandi, Lukman; Sappaile, Baso Intang; Warwer, Fredrik; Widianingsih, Betti; Nugroho, Wahyu; Yana, Medi; Kirom, Ahmad (Civiliza Publishing, Indonesia., 2023)
I am using educational game tools as learning media in playing while learning is an important topic in children's education. As an artificial intelligence, I cannot provide an analysis of this discussion because I cannot evaluate the truth of the debate or research methodology. This research analyzes educational game tools as learning media in playing while teaching activities. This research uses a descriptive qualitative method. Triangulation is the method used, which includes interviews, observation, and documentation. The findings of this study are that the use of educational game tools in learning can increase children's interest and motivation in learning and help develop children's social, cognitive, and motor skills. I am using educational game tools as learning media in playing activities while learning has great potential to improve children's learning. However, parents and teachers must do it properly and support its use. Further research must be done to reveal its potential, limitations, and influence on the child's development.